Genetic Diversity Analysis of 53 Indonesian Rice Genotypes using 6K Single Nucleotide Polymorphism Markers - Joko Prasetiyono; Nurul Hidayatun; Tasliah Tasliah (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
Indonesia is rich in rice genetic resources, however, only a small number has been used in variety improvement programs. This study aimed to determine the genetic diversity of Indonesian rice varieties using 6K SNP markers. The study was conducted at ICABIOGRAD for DNA isolation and IRRI for SNP marker analysis. Genetic materials were 53 rice genotypes consisting of 49 varieties and 4 check genotypes. SNP markers used were 6K loci. Results showed that among the markers analyzed, only 4,606 SNPs (76.77%) were successfully read. The SNP markers covered all twelve rice chromosomes of 945,178.27 bp. The most common allele observed was GG, whereas the least allele was TG. Dendrograms of the 53 rice varieties analyzed with 4,606 SNPs demonstrated several small groups containing genotypic mixtures between indica and japonica rice, and no groups were found to contain firmly indica or japonica type. Structure analysis (K = 2) with value of 0.8 showed that the 53 rice varieties were divided into several groups and each group consisted of 4 japonica, 2 tropical japonica, 46 indica, and 1 aus rice type, respectively. IR64 and Ciherang proved to have an indica genome, while Rojolele has japonica one. Dupa and Hawara Bunar, usually grouped into tropical japonica rice, were classified as indica type, and Hawara Bunar has perfectly 100% indica type. The results of this study indicated that rice classification (indica-japonica) which is usually classified based only on morphological characters, e.g. grain and leaf shapes, is not enough and classification based on SNP markers should be considered for that purpose.